2009
DOI: 10.1021/nn900750w
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Monolayer Gradients in Surface Energy and Surface Chemistry for Block Copolymer Thin Film Studies

Abstract: We utilize a vapor deposition setup and cross-diffusion of functionalized chlorosilanes under dynamic vacuum to generate a nearly linear gradient in surface energy and composition on a silicon substrate. The gradient can be tuned by manipulating chlorosilane reservoir sizes and positions, and the gradient profile is independent of time as long as maximum coverage of the substrate is achieved. Our method is readily amenable to the creation of gradients on other substrate surfaces, due to the use of vapor deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 32 publications
1
98
0
Order By: Relevance
“…The total, dispersive, and polar surface energy components of the bare silica and chlorosilanemodified substrates used in this study are listed in Table 1 and match well with reported measurements found in the literature. 15,16,31,48 Gradient thickness PMMA-PnBA films were coated onto modified substrates via flow coating to determine commensurate and incommensurate thicknesses. 47 Substrate Wetting Behavior Determined by Total Surface Energy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The total, dispersive, and polar surface energy components of the bare silica and chlorosilanemodified substrates used in this study are listed in Table 1 and match well with reported measurements found in the literature. 15,16,31,48 Gradient thickness PMMA-PnBA films were coated onto modified substrates via flow coating to determine commensurate and incommensurate thicknesses. 47 Substrate Wetting Behavior Determined by Total Surface Energy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Each contact angle was measured <0.5 s after each droplet first came into contact with the PB surface. 33 A minimum of five contact angles per sample were measured. The average value of these angles was used in the interfacial tension calculations.…”
Section: Methodsmentioning
confidence: 99%
“…[ 20 , 23 ] Specifi cally, one way to change the surface affi nity is to modify the surface using a polymer brush. [ 20 ] Recently, Albert et al [ 23 ] created a gradient with chemical functionalities that mimics the structures of PS and PMMA, and demonstrated the utility of the fabricated gradient in a PSb -PMMA thin fi lm morphology study in which they identifi ed the expected morphological changes across the gradient. Another approach to tune surface affi nity is based on the use of different solvent vapor treatments.…”
Section: Introductionmentioning
confidence: 99%